Peran orang tua dalam meningkatkan minat belajar siswa di SDN 1 Air Bakoman kabupaten Tanggamus - Mazdayani Multazam; Handayani Setyowati; Andi Sugiratu (Universitas Muhammadiyah Magelang, 2022)
The purpose of this study was to determine the role of parents in increasing the learning interest of class students at SDN 1 Air Bakoman, Pulau Panggung District, Tanggamus Regency. The method used in this research is descriptive qualitative research method with data collection techniques using observations, interviews, and field notes. In this study, the researchers concluded that the role of parents in children's learning interests is very large, especially if the learning process is carried out at home. Parents who help the school in delivering subject matter and doing daily assignments and tests act as motivators so that children are not lazy; so that their achievements will continue to grow and improve. Keywords: Interest in Learning; Role of Parents; Islamic Religious Education Subjects